Comparative Analysis of In-Situ Left Internal Mammary Artery and Saphenous Vein Composite Grafts for Left Anterior Descending Artery Revascularization: A Propensity-Matched Study - Solanki, Parth Bharat; Vadodaria, Nivedita; Solanki, Smit Bharat; Kanzaria, Hitendra (Ukrainian Journal of Cardiovascular Surgery, 2025)
Aim. This study aimed to evaluate the early and mid-term outcomes of a novel strategy using the in-situ left internal mammary artery (LIMA) with a great saphenous vein graft (SVG) to bypass the left anterior descending artery (LAD) in coronary artery bypass grafting (CABG). Materials and methods. A total of 1,240 patients were included in this retrospective observational study. Using propensity-score matching, 155 patients were assigned to the LIMA + SVG group and 155 to the LIMA − LAD group. Early mortality, postoperative complications, and mid-term major adverse cardiovascular and cerebrovascular events (MACCE) were compared between the two matched groups following the procedure. Results. No significant differences were observed in early mortality rates between the LIMA + SVG group and the LIMA − LAD group (3.2 % vs. 2.6 %, P=0.69). For mid-term outcomes, the incidence of MACCE was slightly higher in the LIMA + SVG group, but this difference was not statistically significant (14.2 % vs. 12.3 %, hazard ratio = 1.18, 95% CI, 0.38 to 6.72; P=0.73). Computed tomography coronary artery angiography (CTCA) revealed a LIMA + SVG composite graft patency rate of 93 % (72/77) at 25 months post-procedure. Conclusions. The use of in-situ LIMA with SVG to revascularize LAD was associated with comparable early and mid-term outcomes to using LIMA alone. These findings suggest that the LIMA + SVG composite graft may be a viable alternative strategy when LIMA alone cannot adequately bypass the LAD, particularly in emergency settings.